Characteristics of Sardin Fish Oil (Sardinella sp .) Resulted from Stratified Purification - Dini Wulan Dari; Made Astawan; Sugeng Heri Suseno (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Fish oil production in Indonesia is not only directly sourced from fish raw materials, but also could beprocessed from by-products of canning and fish meal through purification process. The result of purificationwith one process was not satisfy yet for the parameter oxidation quality. Therefore, fish oil from by-productsof fish meal needs to be purified more intensively, such as stratified purification. The aim of this study wasto improve the quality of fish oil from by-product through stratified purification. The multilevel purificationof once purification (P1), twice purification (P2), and three times purification (P3) gives varying results onphysical properties, oxidation parameters, and fatty acid profiles. The color of the brightest fish oil was foundin sample P2, the lowest density was found in sample P3 (0.63 g /cm3), the highest yield was in P1 sample(44.42%), FFA was lowest in P3 sample (0.37%), The lowest PV was in the P1 sample (25.59 meq / kg),the lowest TOTOX was in the P1 sample (48.11 meq / kg), and the highest PUFA content in the fatty acidcomposition was found in sample P2 (37.02%). Purified sardine oil from by-products of fish meal conductedby three-stage purification, which parameters have met the criteria of IFOS 2014 standards, while for PV,AnV, and TOTOX parameters have met IFOMA standards.